Finite element modelling and calibration of a shake rig for durability verification - Rohan, Choudhury Dipesh; Vaidya, Shruti Laxmikant (My University, 2019)
This study is about calibration of the finite element model of the 7-post durability shake rig at Volvo GTT, Lundby. The study was carried out to compare the dynamic behaviour of the physical rig with its finite element model and establish a correlation between them. The calibration is done against experimental data obtained from experimental modal analysis (EMA) by employing an optimization algorithm based on the minimization of the deviation metric between the transfer functions of the parametrized finite element model and the physical rig. The system is excited in two different setups: Hammer Test and 7-post rig test. In hammer test, force input is given while in 7-post rig test displacement input is given. Force is measured for corresponding displacement input using force transducers. Signal processing is done to experimental data. Frequency response functions are synthesized from the accelerance data of the EMA. Post-screening of the measured experimental data is done to cure test data of any errors in estimation. The system is identified using state-space method. The accuracy of the state-space model is improved by developing a MATLAB script that captured the relevant eigenmodes of the identified system. The finite element model is calibrated based on the identified state-space model. The dynamics of the calibrated model is found to be close to the physical rig. The calibrated model improved the correlation of fourth flexible eigenmode while retaining the behaviour of the first three eigenmodes.
Keywords: Experimental Modal Analysis; Frequency response function; 7-post Test Rig; Hammer Test; system identification; calibration